Insight into the Irreversibility and Error Analysis of Nanofluid Flow over Melting Stretching Surface in Porous Media: A Spectral Approach - RamReddy, Ch.; Sweta; Pranitha, J. (Journal of Applied Nonlinear Dynamics, 2026)
This study investigates the flow characteristics of a nanofluid composed of nickel zinc ferrite $(NiZnFe_2O_4)$ and SAE 20W40 motor oil (Society of Automotive Engineers) within a porous medium while optimizing entropy on a stretchable sheet. Such simulations play a crucial role in assessing cooling or heating rates at electromagnetic interfaces, industrial equipment (like cooling turbine blades and combustion systems), orthopedic joint replacements, aircraft turbines, bone plates, and tumor treatments. Irreversibility analysis is developed, considering factors like partial slip, melting, and viscous dissipation to scrutinize various properties of the nanofluid flow. The nanoparticle volume fraction characterizes the nanofluid's behavior. A spectral local linearization method is employed to solve the highly nonlinear ODEs (Ordinary Differential Equations) resulting from Lie group analysis. The study explores the effects of relevant parameters on streamline visualization and physical quantities (surface friction, heat transmission rate, entropy generation, and Bejan number), validating them against existing literature. Results indicate that higher volume fractions lead to reduced friction, the melting parameter helps to increase heat transmission (by $37.98%$) and reduce entropy (by 61.72%).